UMA ANÁLISE DAS TRÊS PRINCIPAIS FESTAS JUDAICAS A PARTIR DE DEUTERONÓMIO 16,1-17 - LESSI, SILVANO TANSINI (2017)
The research deals with the three most important Judaic Feasts: The Feast of Pesah ( Feast of Unleavened Bread), The Feast of Weeks and the Feast of Tabernacles, with a theoretical basis that has the view of the biblical books of The Old Testaments. As backdrop, this research has used the content of Deuteronomy 16, 1-17. It's said that it wasn't for sure when each of these feasts appeared, but it was said that these feasts have suffered alterations in the course of time until nowadays. The comparisons made through the study of the texts in The Old Testaments have given a better view about these alterations. The unification of The Feast of Pesah with The Feast of Unleavened bread since they were close by each other in the Judaic calendar was one of the most important alterations. Another one was the centralization of the three important feasts in the temple of Jerusalem. The analysis also shows the impacts that these changes have caused over the people of Israel. The people who used to celebrate the feasts in a familiar surrounding had to change the place of their worship. The change made by King Josiah also had a great impact over the Jewish people. It's said that such change had a political and economic reason. At last, it was analyzed the changes that had occurred in the calendar of the feasts. The Feast of Pesah which used to be celebrated in the month of Tisri was then celebrated in the month of Abib, in Deuteronomy 16, 1-17.